THE ROLE OF ECONOMIC GROWTH IN INCREASING EMPLOYMENT IN UZBEKISTAN (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the relationship between economic growth and employment in Uzbekistan, employment in economic sectors, effective employment, and the extent to which economic growth meets the need to increase the number of jobs and improve labor productivity. The main directions of increasing employment in Uzbekistan are highlighted.